Judicial system and legal proceedings of the Hetmanate (second half of the 17th – first half of the 18th centuries) - Rumyantsev, V. O.; Hotsuliak, S. L. (Problems of legality, 2021)
The article identifies and characterizes the main stages of formation and transformation of the judicial system and the judiciary of the Hetmanate. The years of independence of the Ukrainian state are marked by rapid changes in the judicial system. The desire of national law to eliminate gaps, determines the interest in the legal past, namely, awareness of the need to reproduce an objective picture of the emergence and evolution of national justice to determine the main directions of its further development. In this regard, the analysis of the judicial system and the judicial process in the Ukrainian lands of the second half of the XVII – first half of the XVIII century. Is useful in some respects. First, an important factor is the appeal to the history of the Ukrainian judicial system, namely the period of the second half of the XVII – first half of the XVIII century, which was decisive for the formation of Ukrainian law as a prototype of European. Secondly, in recent decades there has been an accumulation of significant theoretical and scientific value, which requires a theoretical rethinking of many facts and phenomena. The relevance of the study lies in the accumulation of a large amount of information to reproduce an objective picture of the provisions of the judiciary, which can significantly affect the evolution of the national judicial system and determine its further development. The purpose of the article is to study the structures of the judicial system of the Hetmanate in the second half of the XVII – first half of the XVIII century., And highlight the main features of the judiciary. Issues related to the organization of the judicial system and forms of justice in the Hetmanate in the second half of the XVII – first half of the XVIII century are considered and analyzed. The legal aspects of the organization and activity of various institutions of the judicial system, their jurisdiction and instance are also analyzed. The most significant provisions of the proceedings are highlighted: preliminary investigation, procedure for consideration of the case, evidence, court decisions, the procedure for their appeal and execution.